Rapid Detection of Chlorpheniramine Maleate in Human Blood and Urine Samples Based on NiCoP/PVP/PAN/CNFs Electrochemiluminescence Sensor - Yi Zhang; Jiayu Zhao; Jiaxing Chen; Tingfan Tang; Hao Cheng (Molecules, 2025)
Chlorpheniramine maleate (CPM) is a first-generation antihistamine that is frequently used to treat allergic reactions. However, excessive consumption presents potential health risks. Therefore, it is crucial to develop a quick and precise technique for identifying CPM levels. In this study, nickel cobalt phosphide (NiCoP), a binary metal phosphide, was successfully incorporated into carbon nanofibers. This involved creating a pore structure by adding polyvinylpyrrolidone (PVP) as a pore-forming template to a polyacrylonitrile (PAN) substrate via electrostatic spinning. An innovative electrochemiluminescent sensor for CPM detection was constructed using NiCoP/PVP/PAN carbon nanofibers (NiCoP/PVP/PAN/CNFs). Under optimal conditions, the electrochemical behavior of CPM was studied using NiCoP/PVP/PAN/CNF-modified working electrodes. These findings demonstrate that the three-dimensional porous network architecture of NiCoP/PVP/PAN/CNFs enhances the conductive properties of the material. Consequently, an electrochemical optical sensor fabricated using this structure exhibited remarkable performance. The linear detection range of the sensor was 1 × 10−8–7 × 10−5 mol/L, and the detection limit was 7.8 × 10−10 mol/L. When human urine and serum samples were examined, the sensor was found to have a high recovery rate (94.35–103.36%), which is promising for practical applications.